2022
DOI: 10.1186/s12943-022-01555-3
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of lncRNA MIR100HG with hnRNPA2B1 facilitates m6A-dependent stabilization of TCF7L2 mRNA and colorectal cancer progression

Abstract: Background Epithelial-to-mesenchymal transition (EMT) is a process linked to metastasis and drug resistance with non-coding RNAs (ncRNAs) playing pivotal roles. We previously showed that miR-100 and miR-125b, embedded within the third intron of the ncRNA host gene MIR100HG, confer resistance to cetuximab, an anti-epidermal growth factor receptor (EGFR) monoclonal antibody, in colorectal cancer (CRC). However, whether the MIR100HG transcript itself has a role in cetuximab resistance or EMT is un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 67 publications
2
66
0
Order By: Relevance
“…Interestingly, elevated lncRNAs in the low-risk group are generally considered oncogenic agents in other tumor types. MIR100HG promotes EMT, tumor invasion and metastasis of colorectal cancer cells (Liu et al, 2022). LINC00339, a highly expressed lncRNA in a Frontiers in Genetics frontiersin.org variety of malignant diseases, such as digestive system tumors, respiratory system tumors and nervous system tumors, is associated with the proliferation, motility and invasion of tumor cells (Wu Z. et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, elevated lncRNAs in the low-risk group are generally considered oncogenic agents in other tumor types. MIR100HG promotes EMT, tumor invasion and metastasis of colorectal cancer cells (Liu et al, 2022). LINC00339, a highly expressed lncRNA in a Frontiers in Genetics frontiersin.org variety of malignant diseases, such as digestive system tumors, respiratory system tumors and nervous system tumors, is associated with the proliferation, motility and invasion of tumor cells (Wu Z. et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies showed that hnRNPs were closely related to the occurrence and development of tumors. Recent studies showed that the interaction of the lncRNA MIR100HG with hnRNPA2B1 promoted m6A-dependent TCF7L2 mRNA stabilization and colorectal cancer progression [ 174 ]. HNRNPA2B1 recognizes the m6A site on ILF3 mRNA to stabilize ILF3 mRNA, leading to increased ILF3 expression and promoting the malignant progression of lymphoma [ 175 ].…”
Section: Writers Erasers Readersmentioning
confidence: 99%
“…Furthermore, hnRNPA2B1 binds with MIR100HG and maintains the mRNA stability of TCF7L2. hnRNPA2B1 identifies the TCF7L2 mRNA m6A site via the MIR100HG hnRNPA2B1/TCF7L2 axis and enhances CRC resistance to cetuximab ( Liu et al, 2022b ). Therefore, targeted therapy combined with MIR100HG and immune checkpoint blockade could be a potential therapeutic strategy to improve the immunotherapy response of patients with CRC.…”
Section: Effects Of N6-methyladenosine On Drugs In Tumour Therapymentioning
confidence: 99%